Propyl-2-(8-(3,4-Difluorobenzyl)-2′,5′-Dioxo-8-Azaspiro[Bicyclo[3.2.1] Octane-3,4′-Imidazolidine]-1′-yl) Acetate Induces Apoptosis in Human Leukemia Cells through Mitochondrial Pathway following Cell Cycle Arrest - Kavitha, Chandagirikoppal V.; Nambiar, Mridula; Narayanaswamy, Pavan B.; Thomas, Elizabeth; Rathore, Ujjwal; Ananda Kumar, Channapillekoppalu S.; Choudhary, Bibha; Rangappa, Kanchugarakoppal S.; Raghavan, Sathees C. (PLOS ONE, 2013)
Background Due to the functional defects in apoptosis signaling molecules or deficient activation of apoptosis pathways, leukemia has become an aggressive disease with poor prognosis. Although the majority of leukemia patients initially respond to chemotherapy, relapse is still the leading cause of death. Hence targeting apoptosis pathway would be a promising strategy for the improved treatment of leukemia. Hydantoin derivatives possess a wide range of important biological and pharmacological properties including anticancer properties. Here we investigated the antileukemic activity and mechanism of action of one of the potent azaspiro hydantoin derivative, (ASHD). Materials and Methods To investigate the antileukemic efficacy of ASHD, we have used MTT assay, cell cycle analysis by FACS, tritiated thymidine incorporation assay, Annexin V staining, JC1 staining and western blot analysis. Results Results showed that ASHD was approximately 3-fold more potent than the parent compounds in inducing cytotoxicity. Tritiated thymidine assay in conjunction with cell cycle analysis suggests that ASHD inhibited the growth of leukemic cells. The limited effect of ASHD on cell viability of normal cells indicated that it may be specifically directed to cancer cells. Translocation of phosphatidyl serine, activation of caspase 3, caspase 9, PARP, alteration in the ratio of BCL2/BAD protein expression as well as the loss of mitochondrial membrane potential suggests activation of the intrinsic pathway of apoptosis. Conclusion These results could facilitate the future development of novel hydantoin derivatives as chemotherapeutic agents for leukemia.